2008
DOI: 10.1007/s10336-008-0314-x
|View full text |Cite
|
Sign up to set email alerts
|

Nest placement and nesting success in two finch species colonizing a recently established plantation in an arid region

Abstract: This study examines variations in nest placement and its effects on nesting success in the Desert Finch (Rhodospiza obsoleta) and the Linnet (Carduelis cannabina) which coexist in a recently established plantation (novel habitat) in a desert region in Jordan. A comparison with other habitats (old plantation in the desert and native, Mediterranean-type, habitat of the Linnet) showed that each species displayed similarity in nest placement patterns across habitats. Nest concealment predicted nesting outcome in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The form and colour of MG nests therefore appears to be adaptive in the salt flat environment. These results support the contention that habitat type and nest concealment influence nest predation rates (e.g., Collias & Collias 1984, Martin 1993, 1998, Götmark et al 1995, Lambert & Kleindorfer 2006, Khoury et al 2009). Salt flats may represent a relatively safe breeding haven for many birds.…”
Section: Discussionsupporting
confidence: 86%
“…The form and colour of MG nests therefore appears to be adaptive in the salt flat environment. These results support the contention that habitat type and nest concealment influence nest predation rates (e.g., Collias & Collias 1984, Martin 1993, 1998, Götmark et al 1995, Lambert & Kleindorfer 2006, Khoury et al 2009). Salt flats may represent a relatively safe breeding haven for many birds.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, we did not find differences in clutch size between Tabernas and North Africa, what mirrors the results obtained by Khoury et al (2009) with Desert Finches (Rhodospiza obsoleta) and Linnets (Carduelis cannabina) in new habitats from Jordan. Other studies found an effect of recent colonization on clutch size reduction as shown by Bachir et al (2008) with an expanding population of Cattle Egret (Bubulcus ibis) in Algeria.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the difference in daily survival rates between the incubation and nestling period was not uncommon (Kelleher and O'Halloran 2006;Hanane and Baamal 2011;Bensouilah et al 2014). In addition, other researchers found that the type of habitat (Khoury, Janaydeh, and Al-Hmoud 2009;Hanane and Baamal 2011) and microhabitat selection (Martin and Roper 1988;Wilson and Cooper 1998) had great impact on nest survival. Also, Kelleher and O'Halloran (2006) determined that the daily survival rate of the Song Thrush Turdus philomelos differed between the first and second broods.…”
Section: Discussionmentioning
confidence: 97%
“…on the Laughing Dove's nest. Likewise, Khoury, Janaydeh, and Al-Hmoud (2009) noted that mature olive trees grant access for ground-dwelling predators to some nests in the canopy. In fact, the placement of nests in the central position in the canopy provides best concealment and, consequently, ensures high nesting success, which was not uncommon in the birds surveyed (Murphy 1983;Alonso, Muñoz-Pulido, and Bautista 1991;Boukhriss and Selmi 2009;Khoury, Janaydeh, and Al-Hmoud 2009;Bensouilah et al 2014).…”
Section: Discussionmentioning
confidence: 97%